Determination of intensity and spread of light to the surrounding in conventional phototherapy and comparison with novel converging photo unit - an observational study - Sushma Krishnegowda; Deepti Thandaveshwara; Srinivasa Murthy Doreswamy (SpringerOpen, 2023)
Abstract Background Blue light phototherapy used extensively in the management of hyperbilirubinemia has many side effects like dry eyes, blurring, headache, and altered circadian rhythm. Healthcare providers working around the phototherapy are unduly exposed to these side effects. Altered circadian rhythm results in disruption in the sleep-wake cycle affecting healthcare providers particularly working during the night shift. The constant glare of the blue light interrupts in clinical observation of the baby on phototherapy. With the intent of providing effective phototherapy with minimal exposure of blue light to healthcare providers, a light source called the photo unit was designed and developed. The objective of this study was to estimate the intensity and spread of blue light to the surrounding in conventional phototherapy and to compare the same with newly developed converging photo unit. Results The therapeutic range of irradiance was noted up to 22 inch in diameter with conventional phototherapy compared to only 7 inch with our photo unit. The light spread with a conventional phototherapy unit was seen beyond 50 inch in all directions whereas was confined to 19-inch diameter with photo unit. Conclusion Photo unit developed by the authors has minimal divergence of light to the surrounding, thereby mitigating the side effects of blue light exposure to the people working in the vicinity. Multiple of these photo units can be used to make a phototherapy device.